Knowledge management readiness index: multiple industries perspective - Mohamed Razi, Mohamed Jalaldeen; Mohd Tamrin, Mohd Izzuddin; Ahmad Dahlan, Abdul Rahman; Mohamad Ali, Noor Azian; Habibullah, Md (IEEE, 2018)
The objectives of this paper is to validate a common research instrument and a hypothesized research model to measure the readiness of organizational members to involve in Knowledge Management (KM) process in two different sectors; corporate sector and academic sector. Using the theory of reason action and the theory of planned behavior a conceptual theoretical framework was developed and the related previous works help to operationalize the variables. Data were collected using a questionnaire from two different sectors; 156 academics from a Malaysian university and 74 corporate executives who are working in the IT field in Malaysia. Smartpls3 was used to analyze the data. Convergent validity was tested through factor loadings, composite reliability and average variance extracted while divergent validity was established through discriminant validity separately for each sector. Most of the items and variables meet the respective threshold values in both sectors. The path analysis confirmed that out of seven proposed hypotheses in this study, four are supported in both sectors; IT support, Performance Expectancy, and Effort Expectancy influence KM Intention, in turn, KM Intention influence KM Behavior. The influence of trust among colleagues on KM intention was supported only in the academic dataset. The implications of the findings are discussed at the end of the paper.